Transcriptomic and metabolomic analysis reveals the influence of carbohydrates on lignin degradation mediated by Bacillus amyloliquefaciens - Li, Xiaodan; Li, Zhuofan; Li, Ming; Li, Jingwen; Wang, Quan; Wang, Shuxiang; Li, Shuna; Li, Hongya (Frontiers in Microbiology, 2024)
Ligninolytic bacteria can secrete extracellular enzymes to depolymerize lignin into small-molecular ar-omatics that are subsequently metabolized and funnelled into the TCA cycle. Carbohydrates, which are the preferred carbon source of for bacteria, influence the metabolism of lignin-derived aromatics through bac-teria. In this study, untargeted metabolomics and transcriptomics were performed to investigate the effect of carbohydrates on lignin degradation mediated by Bacillus amyloliquefaciens MN-13, a strain with lig-nin-degrading activity that was isolated in our previous work. The results demonstrated that the cell growth of the MN-13 strain and lignin removal were promoted when carbohydrates such as glucose and sodium carboxymethyl cellulose were added to AL-MSM culture. Metabolomics analysis showed that lignin depol-ymerization took place outside cells, and the addition of glucose regulated the uptake and metabolism of lignin-derived monomers, and activated the downs-stream metabolism process in cells. In the transcriptom-ics analysis, a total of 299 DEGs were screened after 24 h of inoculation in AL-MSM with free glucose and 2 g/L glucose, respectively, accounting for 8.3% of the total amount of annotated genes. These DEGs were primarily assigned to 30 subcategories, including flagellar assembly, the PTS system, RNA degradation, glycolysis/ -gluconeogenesis, the TCA cycle, pyruvate metabolism, tryptophan metabolism, etc. These sub-categories were closely associated with the cell structure, generation of cellular energy and precursors for biosynthetic pathways, based on a −log 10 (P adjust) value in the KEGG pathway analysis. In summary, the addition of glucose increased lignin degradation mediated by the MN-13 strain by regulating glycolysis, the TCA cycle and central carbon metabolism.